Rancang Bangun Akuarium Dengan Pengkondisian PH Air Otomatis Berbasis PLTS - Khoriri, Doddy Nur; Hermawan, Aditya Chandra; Aribowo, Widi; Wardani, Ayusta Lukita (Elposys: Jurnal Sistem Kelistrikan, 2024)
Many people in Indonesia keep freshwater ornamental fish, including guppy fish (Poecilia reticulata), green growth fish (Gyrinocheilus aymonieri), neon tetra fish (Paracheirodon innesi). Neon tetra fish are popular because of their distinctive striking and bright body lines, while guppy fish are kept because of their ease of care and beautiful color variations, especially in male guppies. Guppy fish can grow well at temperatures of 22°C - 27°C and pH 6.5-7.2. Because managers are busy, this becomes an obstacle in fish cultivation, because the water quality that determines fish development becomes unstable. The results of the PLTS output test for 7 days 7 hours per day from 09.00 – 15.00 WIB can charge the battery with an average voltage of 13.89 V and an average current of 1.2 A and an average power of 14.15 W and can run for 24 hours. O'clock. Testing the battery for 7 days and 7 hours from 09.00 – 15.00 WIB can meet power needs for 24 hours with an average battery voltage of 13.36 V and an average current of 0.71 A. Meanwhile, the test results for the servo motor with a feed weight of 2, 45 grams and a servo motor delay of 2 seconds. Testing the pH of the water using a pH pump showed a change from the initial value of 8.06 to 6.91 and was measured with the PH4502C sensor. Tests without a PH pump showed an increase in changes from the initial pH value of 7.76 to 8.05.